Motion control of biped robots in single support phase based on neural network sliding mode approach - Khang, Nguyễn Văn; Trung, Trịnh Quốc (Journal of Computer Science and Cybernetics, 2014)
In this paper, an application of 5-link biped robotic control model is presented through the neural network sliding mode approach. The proposed controller showes efficiency and stability in comparision with the PD controller of biped robots with uncertainties and large noise effects.